Resin composition and molded article
A resin composition with carbon fibers and reinforcing materials like whiskers and granular fillers maintains mechanical strength while improving surface gloss, addressing the gloss deficiency in polyamide resin blends.
Patent Information
- Application Number
- JP2020192238
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2020-11-19
- Publication Date
- 2025-01-15
- Estimated Expiration
- 2040-11-19
AI Technical Summary
Polyamide resin compositions blended with carbon fibers exhibit excellent mechanical strength but suffer from poor surface gloss, which is undesirable for certain applications.
A resin composition comprising 100 parts by mass of polyamide resin, 76 to 120 parts by mass of carbon fiber, and at least one reinforcing material selected from whiskers and granular fillers, with a total mass ratio of carbon fibers and reinforcing materials accounting for 50% or more, and specific ratios of carbon fiber to reinforcing material, along with a polyamide resin composed of diamine-derived and dicarboxylic acid-derived structural units, is used to maintain mechanical strength while enhancing surface gloss.
The composition achieves a balance of high mechanical strength and surface gloss, with gloss values of 45 or more and bending strength of 360 MPa or more, suitable for applications requiring both properties.
Smart Images

Figure 0007613892000001
Abstract
Description
[Technical field]
[0001] The present invention relates to a resin composition and a molded article, and in particular to a resin composition containing a polyamide resin. [Background technology]
[0002] 2. Description of the Related Art Conventionally, attempts have been made to increase the strength of molded articles made of polyamide resin by blending carbon fibers with the polyamide resin. For example, Patent Document 1 discloses a polyamide resin composition containing 100 parts by mass of a polyamide resin having a crystallization half time (ST(P)) of 20 to 500 seconds, 20 to 75 parts by mass of carbon fibers having a number average fiber length of 3 to 10 mm, and whiskers, the amount of whiskers being 20 to 210 parts by mass per 100 parts by mass of carbon fibers having a number average fiber length of 3 to 10 mm. Patent Document 2 discloses a polyamide resin composition containing 20 to 90% by mass of a polyamide resin obtained by reacting xylylenediamine with a linear aliphatic dicarboxylic acid having 6 to 12 carbon atoms, 5 to 60% by mass of carbon fibers, and 5 to 60% by mass of potassium titanate fibers. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] JP 2017-210590 A [Patent Document 2] Japanese Patent Application Publication No. 58-198560 Summary of the Invention [Problem to be solved by the invention]
[0004] Polyamide resin compositions containing carbon fibers are advantageous in that they have excellent mechanical strength, but they have poor surface gloss, although there is a high demand for high surface gloss depending on the application. The present invention has an object to solve the above problems, and to provide a resin composition and a molded article having excellent mechanical strength and high surface gloss. [Means for solving the problem]
[0005] In light of the above-mentioned problems, the present inventors conducted research and found that the above-mentioned problems can be solved by using at least one reinforcing material selected from whiskers and granular fillers in addition to carbon fibers in a polyamide resin and by precisely adjusting the mass ratio thereof. Specifically, the above problems were solved by the following means. <1> A resin composition comprising 100 parts by mass of a polyamide resin, 76 to 120 parts by mass of carbon fiber, and at least one reinforcing material selected from whiskers and granular fillers, wherein the reinforcing material is contained in a total amount of 10 to 120 parts by mass per 100 parts by mass of the carbon fiber, and the total amount of the carbon fiber and the reinforcing material accounts for 50% or more by mass of the entire resin composition. <2> The whiskers have an aspect ratio of 5 to 50. <1> The resin composition according to claim 1. <3> The particulate filler comprises calcium carbonate. <1> or <2> The resin composition according to claim 1. <4> The mass ratio of the carbon fiber to the reinforcing material, carbon fiber / reinforcing material, is 4.3 or less; <1> ~ <3> 10. The resin composition according to claim 9 . <5> the polyamide resin is composed of diamine-derived structural units and dicarboxylic acid-derived structural units, 70 mol % or more of the diamine-derived structural units are derived from at least one of metaxylylenediamine and paraxylylenediamine, and 70 mol % or more of the dicarboxylic acid-derived structural units are derived from an α,ω-linear aliphatic dicarboxylic acid having 4 to 20 carbon atoms; <1> ~ <4> 10. The resin composition according to claim 9 . <6> The α,ω-linear aliphatic dicarboxylic acid having 4 to 20 carbon atoms includes adipic acid and / or sebacic acid. <5> The resin composition according to claim 1. <7> The α,ω-linear aliphatic dicarboxylic acid having 4 to 20 carbon atoms includes adipic acid. <5> The resin composition according to claim 1. <8> The polyamide resin further comprises polyamide 66. <5> ~ <7> 10. The resin composition according to claim 9 . <9> Further comprising a black colorant, <1> ~ <8> 10. The resin composition according to claim 9 . <10> The resin composition was molded into a plate of 100×100×2 mmt, and the L * The value is 24 or greater, <1> ~ <9> 10. The resin composition according to claim 9 . <11> <1> ~ <10> 2. A molded article formed from the resin composition according to claim 1. Effect of the Invention
[0006] The present invention makes it possible to provide a resin composition and a molded article having excellent mechanical strength and high surface gloss. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0007] Hereinafter, an embodiment of the present invention (hereinafter, simply referred to as "the present embodiment") will be described in detail. Note that the present embodiment is an example for explaining the present invention, and the present invention is not limited to the present embodiment. In this specification, the use of "to" means that the numerical values before and after it are included as the lower limit and upper limit. In this specification, various physical properties and characteristic values are those at 23° C. unless otherwise specified. In cases where the standards shown in this specification differ depending on the year and the measurement method, etc., the standards shall be those in effect at the time of filing, unless otherwise stated.
[0008] The resin composition of the present embodiment is a resin composition containing 100 parts by mass of polyamide resin, 76 to 120 parts by mass of carbon fiber, and at least one reinforcing material selected from whiskers and granular fillers, characterized in that the reinforcing material is contained in a total of 10 to 120 parts by mass relative to 100 parts by mass of the carbon fiber, and the total amount of the carbon fiber, the whiskers, and the granular fillers accounts for 50% by mass or more of the entire resin composition. In this way, by blending the carbon fiber and at least one reinforcing material selected from whiskers and granular fillers with the polyamide resin and precisely adjusting the ratio of these, a resin composition having excellent mechanical strength and high surface gloss can be obtained.
[0009] That is, when carbon fiber is blended with polyamide resin, the mechanical strength is improved. However, the surface gloss (gloss value) is reduced. On the other hand, when the amount of carbon fiber is reduced, the surface gloss is improved but the mechanical strength is reduced. It is also possible to replace carbon fiber with glass fiber or wollastonite, but the mechanical strength is reduced compared to when carbon fiber is used. In particular, while glass fiber and wollastonite are known as reinforcing materials, their high bending properties may not be sufficient depending on the application. As a result of the inventor's research, it has been found that by adjusting the amount of carbon fiber and compounding at least one reinforcing material selected from whiskers and granular fillers, it is possible to maintain a high level of mechanical strength without reducing the surface gloss.
[0010] <Polyamide resin> The resin composition of the present embodiment contains a polyamide resin. The type of polyamide resin used in the present embodiment is not particularly limited, and may be an aliphatic polyamide resin, a semi-aromatic polyamide resin, or a blend thereof. For example, the description of the polyamide resin can be found in paragraphs 0011 to 0013 of JP 2011-132550 A. Examples of the aliphatic polyamide resin include polyamide 6 and polyamide 66, with polyamide 66 being preferred. The polyamide resin used in this embodiment preferably contains a semi-aromatic polyamide resin. For example, it is preferable that 80% by mass or more (preferably 85 to 95% by mass) of the polyamide resin contained in the resin composition of this embodiment is a semi-aromatic polyamide resin. Here, the semi-aromatic polyamide resin is composed of a diamine-derived structural unit and a dicarboxylic acid-derived structural unit, and 20 to 80 mol% of the total structural units of the diamine-derived structural unit and the dicarboxylic acid-derived structural unit are structural units containing an aromatic ring. By using such a semi-aromatic polyamide resin, the mechanical strength of the obtained resin molded product can be increased. Examples of the semi-aromatic polyamide resin include terephthalic acid-based polyamide resins (polyamide 6T, polyamide 9T, polyamide 10T) and xylylenediamine-based polyamide resins described later.
[0011] The polyamide resin used in the present embodiment is composed of a diamine-derived structural unit and a dicarboxylic acid-derived structural unit, and it is preferable that 70 mol % or more of the diamine-derived structural units are derived from at least one of metaxylylenediamine and paraxylylenediamine, and 70 mol % or more of the dicarboxylic acid-derived structural units are derived from an α,ω-linear aliphatic dicarboxylic acid having 4 to 20 carbon atoms. Hereinafter, such a polyamide resin may be referred to as a xylylenediamine-based polyamide resin. By using a xylylenediamine-based polyamide resin, a molded product having excellent mechanical strength can be obtained. The diamine-derived structural units of the xylylenediamine-based polyamide resin are more preferably 75 mol% or more, even more preferably 80 mol% or more, still more preferably 85 mol% or more, even more preferably 90 mol% or more, and still more preferably 95 mol% or more derived from metaxylylenediamine or paraxylylenediamine. In this embodiment, the ratio of meta-xylylenediamine to para-xylylenediamine is preferably 10-100 mol% meta-xylylenediamine and 0-90 mol% para-xylylenediamine, more preferably 0-70 mol% para-xylylenediamine and 30-100 mol% meta-xylylenediamine, even more preferably 0-30 mol% para-xylylenediamine and 70-100 mol% meta-xylylenediamine, still more preferably 0-10 mol% para-xylylenediamine and 90-100 mol% meta-xylylenediamine, and even more preferably 0-2 mol% para-xylylenediamine and 98-100 mol% meta-xylylenediamine. The dicarboxylic acid-derived structural units of the xylylenediamine-based polyamide resin are more preferably 75 mol % or more, even more preferably 80 mol % or more, still more preferably 90 mol % or more, even more preferably 95 mol % or more, and even more preferably 98 mol % or more, of which the dicarboxylic acid-derived structural units are derived from an α,ω-linear aliphatic dicarboxylic acid having 4 to 20 carbon atoms.
[0012] Diamines other than metaxylylenediamine and paraxylylenediamine that can be used as the raw diamine component of the xylylenediamine-based polyamide resin include aliphatic diamines such as tetramethylenediamine, pentamethylenediamine, 2-methylpentanediamine, hexamethylenediamine, heptamethylenediamine, octamethylenediamine, nonamethylenediamine, decamethylenediamine, dodecamethylenediamine, 2,2,4-trimethylhexamethylenediamine, and 2,4,4-trimethylhexamethylenediamine, 1,3-bis( Examples of the diamines include alicyclic diamines such as bis(aminomethyl)cyclohexane, 1,4-bis(aminomethyl)cyclohexane, 1,3-diaminocyclohexane, 1,4-diaminocyclohexane, bis(4-aminocyclohexyl)methane, 2,2-bis(4-aminocyclohexyl)propane, bis(aminomethyl)decalin, and bis(aminomethyl)tricyclodecane; and diamines having an aromatic ring such as bis(4-aminophenyl)ether, paraphenylenediamine, and bis(aminomethyl)naphthalene. These can be used alone or in combination of two or more.
[0013] Examples of α,ω-linear aliphatic dicarboxylic acids having 4 to 20 carbon atoms that are suitable for use as the raw dicarboxylic acid component of the xylylenediamine-based polyamide resin include aliphatic dicarboxylic acids such as succinic acid, glutaric acid, pimelic acid, suberic acid, azelaic acid, adipic acid, sebacic acid, undecanedioic acid, and dodecanedioic acid. One or a mixture of two or more of these can be used. Among these, adipic acid and / or sebacic acid are more preferred, and adipic acid is even more preferred, since the melting point of the polyamide resin falls within a range suitable for molding.
[0014] Examples of dicarboxylic acid components other than the above-mentioned α,ω-linear aliphatic dicarboxylic acids having 4 to 20 carbon atoms include phthalic acid compounds such as isophthalic acid, terephthalic acid, and orthophthalic acid, and isomers of naphthalenedicarboxylic acids such as 1,2-naphthalenedicarboxylic acid, 1,3-naphthalenedicarboxylic acid, 1,4-naphthalenedicarboxylic acid, 1,5-naphthalenedicarboxylic acid, 1,6-naphthalenedicarboxylic acid, 1,7-naphthalenedicarboxylic acid, 1,8-naphthalenedicarboxylic acid, 2,3-naphthalenedicarboxylic acid, 2,6-naphthalenedicarboxylic acid, and 2,7-naphthalenedicarboxylic acid. These can be used alone or in combination of two or more kinds.
[0015] In the present embodiment, the xylylenediamine-based polyamide resin is particularly preferably one in which 70 mol% or more (more preferably 75 mol% or more, even more preferably 80 mol% or more, even more preferably 90 mol% or more, even more preferably 95 mol% or more, and even more preferably 98 mol% or more) of the diamine-derived structural units are derived from meta-xylylenediamine, and 70 mol% or more (more preferably 75 mol% or more, even more preferably 80 mol% or more, even more preferably 90 mol% or more, even more preferably 95 mol% or more, and even more preferably 98 mol% or more) of the dicarboxylic acid-derived structural units are derived from adipic acid.
[0016] In addition, although the diamine-derived structural unit and the dicarboxylic acid-derived structural unit are the main components, it is not necessary to completely exclude other structural units, and it goes without saying that the resin may contain lactams such as ε-caprolactam and laurolactam, and aliphatic aminocarboxylic acid-derived structural units such as aminocaproic acid and aminoundecanoic acid. Here, the main component means that, among the structural units constituting the xylylenediamine-based polyamide resin, the total number of the diamine-derived structural unit and the dicarboxylic acid-derived structural unit is the largest among all the structural units. In this embodiment, the total of the diamine-derived structural unit and the dicarboxylic acid-derived structural unit in the xylylenediamine-based polyamide resin preferably accounts for 90% or more of the total structural units, and more preferably accounts for 95% or more.
[0017] In this embodiment, the polyamide resin preferably contains a xylylenediamine-based polyamide resin and polyamide 66, and more preferably contains 85 to 95 mass% of the xylylenediamine-based polyamide resin and 5 to 15 mass% of polyamide 66. However, the total of the xylylenediamine-based polyamide resin and polyamide 66 does not exceed 100 mass%, and the total of the xylylenediamine-based polyamide resin and polyamide 66 is preferably 95 to 100 mass%, and more preferably 98 to 100 mass%.
[0018] The content of the polyamide resin in the resin composition of the present embodiment is preferably 20% by mass or more, more preferably 25% by mass or more, even more preferably 30% by mass or more, and even more preferably 35% by mass or more. By making it equal to or more than the lower limit, extrudability tends to be more stable. The content of the polyamide resin in the resin composition of the present embodiment is 50% by mass or less, preferably 45% by mass or less, and more preferably 40% by mass or less. By making the content less than the upper limit, the mechanical strength of the resin molded product tends to be further improved. The resin composition of the present embodiment may contain only one type of polyamide resin, or may contain two or more types. When two or more types are contained, the total amount is preferably in the above range.
[0019] The resin composition of the present embodiment may or may not contain a thermoplastic resin other than the polyamide resin. The content of the thermoplastic resin other than the polyamide resin in the resin composition of the present embodiment is preferably 5% by mass or less, more preferably 3% by mass or less, and even more preferably 1% by mass or less of the resin composition of the present embodiment.
[0020] <Carbon fiber> The resin composition of the present embodiment contains 76 to 120 parts by mass of carbon fiber per 100 parts by mass of polyamide resin. By containing the carbon fiber, a resin composition and a molded product having excellent mechanical strength, particularly bending properties, can be obtained. The type of carbon fiber is not particularly limited, and either polyacrylonitrile-based carbon fiber (PAN-based fiber) or pitch-based carbon fiber using pitch is preferably used, with polyacrylonitrile-based carbon fiber (PAN-based fiber) being more preferred.
[0021] The carbon fibers are preferably chopped strands. The carbon fibers have a number average fiber length of preferably 3 mm or more, more preferably 4 mm or more, and preferably 10 mm or less, more preferably 8 mm or less, and even more preferably 7 mm or less. The carbon fibers preferably have a number average fiber diameter of 3 to 20 μm, more preferably 5 to 15 μm. By using carbon fibers in this range, the obtained molded product can have an excellent balance between mechanical strength and appearance. The carbon fibers used may have a tensile strength of 5.0 GPa or less (preferably 3.5 to 5.0 GPa) measured at 23° C. in accordance with JIS R7601. Specific examples of carbon fibers include Torayca manufactured by Toray Industries, Inc., Besfight Filament manufactured by Toho Tenax Co., Ltd., and Pyrofil manufactured by Mitsubishi Rayon Co., Ltd.
[0022] The carbon fiber content in the resin composition of this embodiment is 76 parts by mass or more, preferably 78 parts by mass or more, and may be 81 parts by mass or more, relative to 100 parts by mass of polyamide resin. By making it equal to or more than the lower limit, the bending properties, particularly the bending modulus, of the obtained molded article can be effectively improved. The carbon fiber content in the resin composition of this embodiment is also 120 parts by mass or less, preferably 110 parts by mass or less, more preferably 105 parts by mass or less, further preferably 100 parts by mass or less, and may be 95 parts by mass or less, relative to 100 parts by mass of polyamide resin. By making it equal to or less than the upper limit, the surface glossiness tends to be further improved. In addition, the moldability of the pellets tends to be improved. The resin composition of the present embodiment may contain only one type of carbon fiber, or may contain two or more types. When two or more types are contained, the total amount is preferably within the above range.
[0023] <At least one reinforcing material selected from whiskers and particulate fillers> The resin composition of this embodiment contains at least one type of reinforcing material selected from whiskers and granular fillers (hereinafter simply referred to as the "specific reinforcing material") in a total of 10 to 120 parts by mass per 100 parts by mass of carbon fiber, and further, the total amount of the carbon fiber and the specific reinforcing material accounts for 50% or more by mass of the entire resin composition. By including the specific reinforcing material in the above-mentioned predetermined ratio, it is possible to increase the surface gloss while maintaining high mechanical strength of the resin composition.
[0024] In this embodiment, whiskers can be used as the specific reinforcing material. Whiskers are short fibrous or needle-like inorganic crystals. The whiskers preferably have an aspect ratio of 5 to 50, and more preferably 10 to 40. By setting the aspect ratio within such a range, the appearance of the resulting molded article can be further improved. The number average fiber length of the whiskers is preferably 5 to 200 μm, and more preferably 5 to 150 μm. By setting the length in this range, the appearance of the obtained molded article can be further improved. The number average fiber diameter of the whiskers is preferably 0.1 to 20 μm, and more preferably 0.3 to 15 μm. By setting the diameter within such a range, the appearance of the obtained molded article can be further improved. The number-average fiber length and number-average fiber diameter of the whiskers can be measured by observing them under an electron microscope in a state where they are dispersed in a solvent such as alcohol. Usually, the average value of 100 whiskers is taken.
[0025] The whiskers preferably have a Mohs hardness of 2.5 to 5.0, and more preferably 3.0 to 4.8. By setting the hardness within such a range, wear on the barrel and screw of the extruder can be reduced, enabling stable extrusion. The whiskers preferably have a specific gravity of 2.0 to 4.0, and more preferably 2.2 to 3.8. By using whiskers in such a range, the volume ratio in the molded article becomes smaller, the volume of the resin in the molded article can be increased, and the appearance of the molded article tends to be improved.
[0026] Examples of raw materials for the whiskers include zinc oxide, potassium titanate, aluminum borate, silicon carbide, silicon nitride, magnesium oxide, magnesium borate, basic magnesium sulfate, titanium diboride, graphite, calcium sulfate, α-alumina, chrysotile, wollastonite, aluminum silicate, calcium silicate, titanium oxide, and zirconium oxide. In this embodiment, wollastonite and / or potassium titanate are preferred. By using wollastonite, a molded product with higher rigidity and strength can be obtained without decreasing the surface gloss. By using potassium titanate, a molded product with higher rigidity and strength can be obtained without decreasing the surface gloss.
[0027] The whiskers used in this embodiment may be subjected to a known surface treatment (for example, a surface treatment with a surface treatment agent such as a metal oxide, a silane coupling agent, a titanium coupling agent, an organic acid, a polyol, or silicone.) By subjecting the whiskers to such a surface treatment, it may be possible to improve the compatibility and dispersibility with other components in the resin composition of this embodiment.
[0028] In addition, as the whiskers, for example, commercially available products such as those sold under the trade names "Pana-Tetra WZ-0501", "Pana-Tetra WZ-0501L", "Pana-Tetra WZ-0511", "Pana-Tetra WZ-0511L", "Pana-Tetra WZ-0531", "Pana-Tetra WZ-05E1", and "Pana-Tetra WZ-05F1" (all zinc oxide whiskers, manufactured by Amtec Co., Ltd.); those sold under the trade names "FTL-100", "FTL-110", "FTL-200", and "FTL-300" (all titanium oxide whiskers, manufactured by Ishihara Sangyo Kaisha, Ltd.); and those sold under the trade name "TOFIX-P" (titanium oxide whiskers, manufactured by Toho Titanium Co., Ltd.) can also be used.
[0029] The resin composition of the present embodiment may also use a granular filler as the specific reinforcing material. The granular filler is a filler in the form of particles, and usually has an aspect ratio of less than 5. The granular filler preferably has an average particle size of 0.01 to 2 μm, more preferably 0.05 to 1 μm. By setting the average particle size within this range, the appearance of the resulting molded article can be further improved. The average particle size here refers to the median diameter (D50) determined from a particle size distribution diagram measured with a laser diffraction particle size distribution measuring device.
[0030] The granular filler preferably has a Mohs hardness of 2.5 to 5.0, more preferably 2.5 to 4.5. By setting the hardness within this range, wear on the barrel and screw of the extruder can be reduced, enabling stable extrusion. The granular filler preferably has a specific gravity of 2.0 to 4.0, more preferably 2.2 to 3.8. By using a granular filler in such a range, the volume ratio in the molded article becomes smaller, the volume of the resin in the molded article can be increased, and the appearance of the molded article tends to be improved.
[0031] Examples of raw materials for the granular filler include calcium carbonate and kaolin, with calcium carbonate being preferred. By using calcium carbonate, it is possible to obtain a molded product with higher rigidity and strength without reducing the surface gloss. Examples of calcium carbonate include synthetic calcium carbonate, natural calcium carbonate, and surface-treated calcium carbonate obtained by surface-treating them with silicic acid or an organic acid. For details of calcium carbonate, see paragraphs 0049 to 0054 of JP2019-077778A, the contents of which are incorporated herein by reference.
[0032] The content of the specific reinforcement material in the resin composition of this embodiment is preferably 10 parts by mass or more, and may be 20 parts by mass or more, relative to 100 parts by mass of the polyamide resin. By making it equal to or more than the lower limit, the surface gloss tends to be further improved. The content of the carbon fiber in the resin composition of this embodiment is also preferably 100 parts by mass or less, more preferably 90 parts by mass or less, and may be 60 parts by mass or less, or even 52 parts by mass or less, relative to 100 parts by mass of the polyamide resin. By making it equal to or less than the upper limit, the surface gloss can be effectively improved. The resin composition of the present embodiment may contain only one type of specific reinforcing material, or may contain two or more types. When two or more types are contained, the total amount is preferably within the above range.
[0033] <Carbon fiber and specific reinforcement material content> In the resin composition of this embodiment, the specific reinforcement material is contained in a total of 10 to 120 parts by mass relative to 100 parts by mass of carbon fiber. By making it 10 parts by mass or more, the surface glossiness of the obtained molded article can be increased. In addition, by making it 120 parts by mass or less, the mechanical strength can be increased. The content of the specific reinforcement material is preferably 20 parts by mass or more, more preferably 25 parts by mass or more, even more preferably 40 parts by mass or more, even more preferably 45 parts by mass or more, and even more preferably 50 parts by mass or more, relative to 100 parts by mass of carbon fiber. In addition, the content of the specific reinforcement material is preferably 110 parts by mass or less, more preferably 105 parts by mass or less, even more preferably 90 parts by mass or less, even more preferably 75 parts by mass or less, and even more preferably 65 parts by mass or less, relative to 100 parts by mass of carbon fiber.
[0034] In the resin composition of the present embodiment, the mass ratio of carbon fiber to specific reinforcement, carbon fiber / specific reinforcement, is preferably 4.5 or less, more preferably 4.3 or less, even more preferably 3.5 or less, even more preferably 3.0 or less, even more preferably 2.5 or less, and even more preferably 2.0 or less. By making it below the upper limit, the surface gloss tends to be further improved. In addition, the carbon fiber / specific reinforcement is preferably 0.9 or more, more preferably 1.0 or more, even more preferably 1.2 or more, and even more preferably 1.5 or more. By making it above the lower limit, the elastic modulus and strength tend to be further improved.
[0035] Furthermore, in the resin composition of this embodiment, the total amount of the carbon fiber and the specific reinforcement material accounts for 50% by mass or more of the entire resin composition. By making it 50% by mass or more, the mechanical strength of the obtained molded product can be increased. The total amount of the carbon fiber and the specific reinforcement material is preferably 52% by mass or more, and more preferably 53% by mass or more. Moreover, the total amount of the carbon fiber and the specific reinforcement material is preferably 70% by mass or less of the entire resin composition, more preferably 67% by mass or less, even more preferably 64% by mass or less, even more preferably 62% by mass or less, and even more preferably 58% by mass or less. By making it equal to or less than the upper limit, moldability tends to be further improved.
[0036] <Black colorant> The resin composition of the present embodiment preferably contains a black colorant. By containing a black colorant, it is possible to provide a molded article having high rigidity, high elastic modulus, and excellent appearance.
[0037] The type of black colorant is not particularly limited, but examples include pigments such as carbon black and titanium black, nigrosine and aniline black, with carbon black being preferred. In the resin composition of the present embodiment, by blending carbon black, the carbon black acts as a nucleating agent, and good moldability can be achieved even when a thin-walled molding is performed.
[0038] The carbon black used in the present embodiment may be any conventionally known carbon black. Examples include furnace black, channel black, ketjen black, and acetylene black. Among them, carbon black with DBP absorption of 30 to 300 g / 100 cm3 has excellent hiding power. 3 The use of carbon black, particularly furnace black, is preferred because it allows a stable color tone to be expressed.
[0039] The content of the black colorant in the resin composition of this embodiment is preferably 0.1 parts by mass or more, more preferably 0.5 parts by mass or more, and even more preferably 1 part by mass or more, relative to 100 parts by mass of the polyamide resin. By making it equal to or more than the lower limit, a more stable color tone can be obtained. In addition, the content is preferably 10 parts by mass or less, more preferably 5 parts by mass or less, and even more preferably 4 parts by mass or less. By making it equal to or less than the upper limit, higher mechanical properties tend to be obtained. The resin composition of the present embodiment may contain only one type of black colorant, or may contain two or more types. When two or more types are contained, the total amount is preferably in the above range.
[0040] <Nucleating agent> The resin composition of the present embodiment may contain a nucleating agent to adjust the crystallization rate. The type of nucleating agent is not particularly limited, but talc, boron nitride, mica, kaolin, barium sulfate, silicon nitride, and molybdenum disulfide are preferable, talc and boron nitride are more preferable, and talc is even more preferable. When the resin composition of the present embodiment contains a nucleating agent, the content thereof is preferably 0.01 parts by mass or more, more preferably 0.1 parts by mass or more, and even more preferably 0.5 parts by mass or more, relative to 100 parts by mass of the polyamide resin. The upper limit of the content is preferably 10 parts by mass or less, more preferably 8 parts by mass or less, even more preferably 6 parts by mass or less, and even more preferably 4 parts by mass or less. The resin composition of the present embodiment may contain only one type of nucleating agent, or may contain two or more types. When two or more types are contained, the total amount is preferably in the above range.
[0041] <Release agent> The resin composition of the present embodiment may contain a release agent. Examples of the release agent include aliphatic carboxylic acids, salts of aliphatic carboxylic acids, esters of aliphatic carboxylic acids and alcohols, aliphatic carboxylic acid amides, aliphatic hydrocarbon compounds having a number average molecular weight of 200 to 15,000, polysiloxane-based silicone oils, and waxes. As the wax, polyolefin wax, ketone wax, amide wax, ester wax, and paraffin wax are preferable, and ketone wax is more preferable. For details about the release agent, please refer to the descriptions in paragraphs 0034 to 0039 of JP 2017-115093 A and paragraphs 0068 to 0091 of JP 2018-184575 A, the contents of which are incorporated herein by reference.
[0042] When the resin composition of the present embodiment contains a release agent, the content thereof is preferably 0.05 parts by mass or more, more preferably 0.1 parts by mass or more, and even more preferably 0.2 parts by mass or more, relative to 100 parts by mass of the polyamide resin, and the content is preferably 5 parts by mass or less, more preferably 4 parts by mass or less, and even more preferably 3 parts by mass or less. The resin composition of the present embodiment may contain only one type of release agent, or may contain two or more types. When two or more types are contained, the total amount is preferably in the above range.
[0043] <Other ingredients> The resin composition of the present embodiment may contain other components within the scope of the present embodiment. Examples of such additives include fillers other than carbon fibers and specific reinforcement materials, light stabilizers, antioxidants, flame retardants, flame retardant assistants, ultraviolet absorbers, fluorescent brighteners, drip prevention agents, antistatic agents, antifogging agents, antiblocking agents, flowability improvers, weather resistance improvers, light resistance improvers, plasticizers, dispersants, and antibacterial agents. These components may be used alone or in combination of two or more. The content of these components is preferably in the range of 5% by mass or less of the resin composition. In the resin composition of this embodiment, the contents of the polyamide resin, carbon fiber, and specific reinforcing material, as well as other additives that are blended as necessary, are adjusted so that the total of each component is 100% by mass. In the resin composition of this embodiment, the total of the polyamide resin, nucleating agent, carbon fiber, specific reinforcing material, black colorant, and release agent preferably accounts for 90% by mass or more of the resin composition, more preferably 95% by mass or more, and even more preferably 98% by mass or more.
[0044] <Characteristics of resin composition> The resin composition of the present embodiment is preferably excellent in surface gloss. Specifically, the gloss (Gs60) is preferably 45 or more, more preferably 50 or more, even more preferably 54 or more, even more preferably 58 or more, and even more preferably 60 or more. The upper limit of the gloss (Gs60) is practically 100, and even if it is 80 or less, the required performance is satisfied. The gloss value (Gs60) is measured according to the description in the Examples section described later.
[0045] The resin composition of this embodiment was molded into a plate of 100 × 100 × 2 mmt, and the L * The value is preferably 24 or more, and more preferably 26 or more. * In order to achieve a value of 24 or more, it is preferable to use potassium titanate whiskers as the specific reinforcing material. The resin composition of this embodiment was molded into a plate of 100×100×2 mmt and measured in accordance with JIS K7105. * Preferably, the value is less than 24, more preferably 20 or less, and even more preferably 16 or less. * In order to make the value less than 24, it is preferable to use whiskers or calcium carbonate as the specific reinforcing material. L * The values are measured as described in the Examples section below.
[0046] The resin composition of the present embodiment preferably has a bending strength of 360 MPa or more, more preferably 380 MPa or more, and even more preferably 395 MPa or more at a temperature of 23° C. when molded into an ISO tensile test piece (4 mm thick) in accordance with ISO 178. The upper limit of the bending strength is not particularly set, but 550 MPa or less is practical.
[0047] The resin composition of the present embodiment preferably has a flexural modulus of 32.0 GPa or more, more preferably 35.0 GPa or more, and even more preferably 38.0 GPa or more at a temperature of 23° C. when molded into an ISO tensile test piece (4 mm thick) in accordance with ISO 178. There is no particular upper limit for the flexural modulus, but 55.0 GPa or less is practical, and even 50.0 GPa or less fully satisfies the required performance. The bending strength and bending modulus are measured by the method described in the examples below.
[0048] <Method of producing resin composition> The resin composition of the present embodiment can be produced by a known method for producing a thermoplastic resin composition. As an embodiment of the method for producing the resin composition of the present embodiment, it is preferable to mix and knead the polyamide resin with the carbon fiber and the specific reinforcing material. An example of such a resin composition is pellets. Specifically, the polyamide resin, carbon fiber, specific reinforcing material, and other components to be blended as necessary may be premixed using various mixers such as a tumbler or a Henschel mixer, and then melt-kneaded using a mixer such as a Banbury mixer, a roll, a Brabender, a single-screw kneading extruder, a twin-screw kneading extruder, or a kneader.
[0049] In addition, for example, the resin composition of the present embodiment can be produced by premixing only some of the components (e.g., carbon fiber and a specific reinforcing material) without premixing the components, and feeding the mixture to an extruder using a feeder and melt-kneading the mixture. In addition, for example, some of the components (e.g., a black colorant) can be mixed in advance, fed to an extruder, and melt-kneaded to obtain a composition, which can be used as a master batch. The master batch can then be mixed again with the remaining components and melt-kneaded to produce the resin composition of the present embodiment. In addition, for example, when mixing a component that is difficult to disperse, the dispersibility can be improved by dissolving or dispersing the component in advance in a solvent such as water or an organic solvent, and then kneading the component with the solution or dispersion.
[0050] <Molded products> The molded article of the present embodiment is formed from the resin composition of the present embodiment. The method for producing the molded article of the present embodiment is not particularly limited. For example, the molded product of this embodiment may be produced by melt-kneading the components and then directly molding the components using various molding methods, or by melt-kneading the components and pelletizing them, and then melting them again and molding them using various molding methods.
[0051] The method for molding the molded product is not particularly limited, and any conventionally known molding method can be used, such as injection molding, injection compression molding, extrusion molding, profile extrusion, transfer molding, hollow molding, gas-assisted hollow molding, blow molding, extrusion blow molding, IMC (in-mold coating molding), rotational molding, multi-layer molding, two-color molding, insert molding, sandwich molding, foam molding, and pressure molding.
[0052] The shape of the molded product of the present embodiment is not particularly limited and can be appropriately selected depending on the application and purpose of the molded product. Examples of the shape include plate-like, plate-like, rod-like, sheet-like, film-like, cylindrical, annular, circular, elliptical, gear-like, polygonal, irregularly shaped, hollow, frame-like, box-like, and panel-like shapes.
[0053] The application field of the molded product of this embodiment is not particularly limited, and it is widely used in automobile and other transportation machinery parts, general machine parts, precision machine parts, electronic and electrical equipment parts, office automation equipment parts, building materials and housing related parts, medical devices, leisure sports goods, play equipment, medical products, daily necessities such as food packaging films, defense and aerospace products, etc. In particular, the molded article of the present embodiment is preferably used in applications requiring mechanical strength and gloss. EXAMPLES
[0054] The present invention will be described in more detail below with reference to examples. The materials, amounts, ratios, processing contents, processing procedures, etc. shown in the following examples can be appropriately changed without departing from the spirit of the present invention. Therefore, the scope of the present invention is not limited to the specific examples shown below. If the measuring instruments used in the examples are difficult to obtain due to discontinuation or the like, measurements can be made using other instruments with equivalent performance.
[0055] 1. Raw materials <Polyamide resin> MXD6: Mitsubishi Gas Chemical Company, #6000, melting point 237°C, glass transition temperature 85°C PA66: Polyamide 66, DuPont, Zytel 101NC-10, melting point 265°C, glass transition temperature 55°C <Nucleating agent> Talc: Hayashi Kasei Micron White 5000A
[0056] <Carbon fiber> Carbon fiber: Polyacrylonitrile carbon fiber, manufactured by Mitsubishi Rayon Co., Ltd., Pyrofil TR06NL, tensile strength 4.9GPa, number average fiber diameter 7μm, number average fiber length 6mm
[0057] <Specific reinforcement material> Wollastonite: Tomoe Engineering Co., Ltd., Wollastonite whisker, aspect ratio 17, NYGLOS8-10013, number average fiber length 136 μm, number average fiber diameter 8 μm, Mohs hardness 4.5, specific gravity 2.9 TISMO: Potassium titanate whisker, Otsuka Chemical, TISMO D-101, aspect ratio 30, number average fiber length 15 μm, number average fiber diameter 0.5 μm, Mohs hardness 4.0, specific gravity 3.5 Calcium carbonate: Granular filler, manufactured by Nitto Funka Kogyo Co., Ltd., product number: NS#100, average particle size 2.1μm, Mohs hardness 3.0, specific gravity 2.7
[0058] <Black colorant> Carbon black MB: Carbon black master batch, manufactured by Mitsubishi Chemical, Carbon black #45 (furnace black, DBP absorption 53g / 100cm 3 )
[0059] <Release agent> Release agent: Nitto Kasei Kogyo Co., Ltd., product number: CS-8CP
[0060] 2. Examples 1 to 6 and Comparative Examples 1 to 4 Each component was weighed according to Table 1 described later (each component in Table 1 is expressed in parts by mass), and the components except for the carbon fiber and the specific reinforcement were blended in a tumbler, fed into the base of a twin-screw extruder (Shibaura Machine Co., Ltd., TEM26SS), melted, and kneaded. After kneading, the carbon fiber and the specific reinforcement were side-fed to prepare pellets (resin composition). The extruder was set at a temperature of 280°C. The obtained pellets were used for the following evaluations: In Comparative Example 4, extrusion was difficult, and no pellets were obtained.
[0061] <Bending properties> The pellets were dried at 120°C for 3 hours, and then injection molded into ISO tensile test specimens (4 mm thick) using an injection molding machine (Nissei Plastic Industrial Co., Ltd., "NEX140III") at a cylinder temperature of 280°C and a mold temperature of 130°C. The flexural strength (unit: MPa) and flexural modulus (unit: GPa) were measured using the above ISO tensile test pieces (4 mm thick) in accordance with ISO 178. The results are shown in Table 1.
[0062] <Glossiness (Gs60)> The pellets were dried at 120°C for 3 hours and then injection molded into a 100 x 100 x 2 mmt plate using an injection molding machine (Nissei Plastic Industrial Co., Ltd., "NEX140III") at a cylinder temperature of 280°C and a mold temperature of 130°C. The gloss (Gs60) of the molded product at 60 degrees was measured in accordance with JIS Z8741. The results are shown in Table 1. The measuring machine used was VG8000 manufactured by Nippon Denshoku Industries Co., Ltd.
[0063] <L * Value> The above plate was measured under the following measurement conditions using a color difference meter (SE6000 manufactured by Nippon Denshoku Industries Co., Ltd.) in accordance with JIS K7105. * The values were measured. Measurement conditions: Reflection measurement, C light source / 2°, field of view 30Φ
[0064] [Table 1]
[0065] As is clear from the above results, the resin composition of the present invention had high mechanical strength, high gloss, and excellent surface gloss (Examples 1 to 6). Furthermore, by lowering the mass ratio of carbon fiber to specific reinforcing material (carbon fiber / reinforcing material), a molded product with high surface gloss was obtained. On the other hand, when the amount of carbon fiber was small or not blended (Comparative Examples 1 and 2), the mechanical strength was poor, and when the amount of carbon fiber was too large (Comparative Example 4), extrusion was not possible and pellets were not obtained. Furthermore, when at least one specific reinforcing material selected from whiskers and granular fillers was not blended (Comparative Example 3), the gloss level was low and the surface gloss was poor.
Claims
1. A resin composition comprising 100 parts by mass of polyamide resin, 76 to 120 parts by mass of carbon fiber, and whiskers, The whiskers are contained in a total amount of 10 to 120 parts by mass per 100 parts by mass of the carbon fibers, The total amount of the carbon fibers and the whiskers accounts for 53 mass% or more of the entire resin composition, 80% by mass or more of the polyamide resin contained in the resin composition is a semi-aromatic polyamide resin, and the semi-aromatic polyamide resin is composed of a diamine-derived structural unit and a dicarboxylic acid-derived structural unit, and 20 to 80 mol % of the total structural units of the diamine-derived structural unit and the dicarboxylic acid-derived structural unit are structural units containing an aromatic ring. Resin composition.
2. The resin composition according to claim 1, wherein the whiskers have an aspect ratio of 5 to 50.
3. The resin composition according to claim 1 or 2, wherein a mass ratio of the carbon fibers to the whiskers, carbon fibers / whiskers, is 4.3 or less.
4. The polyamide resin according to any one of claims 1 to 3, wherein the polyamide resin is composed of diamine-derived structural units and dicarboxylic acid-derived structural units, 70 mol % or more of the diamine-derived structural units are derived from at least one of metaxylylenediamine and paraxylylenediamine, and 70 mol % or more of the dicarboxylic acid-derived structural units are derived from an α,ω-linear aliphatic dicarboxylic acid having 4 to 20 carbon atoms.
5. The resin composition according to claim 4, wherein the α,ω-linear aliphatic dicarboxylic acid having 4 to 20 carbon atoms includes adipic acid and / or sebacic acid.
6. The resin composition according to claim 4, wherein the α,ω-linear aliphatic dicarboxylic acid having 4 to 20 carbon atoms includes adipic acid.
7. The resin composition according to any one of claims 4 to 6, wherein the polyamide resin further contains polyamide 66.
8. The resin composition according to any one of claims 1 to 7, further comprising a black colorant.
9. The resin composition was molded into a plate of 100×100×2 mmt, and the L * The resin composition according to any one of claims 1 to 8, wherein the value is 24 or more.
10. A molded article formed from the resin composition according to any one of claims 1 to 9.
Citation Information
Patent Citations
Polyamide resin composition
JP1983198560A
Complex resin composition
JP1994172643A
Polyamide resin composition
JP2006056938A
Polyamide resin composition, molded article, and method for producing polyamide resin composition
JP2017210590A
Fiber-reinforced thermoplastic resin composition, production method thereof and injection molded article
JP2019167502A